2000
DOI: 10.1006/viro.2000.0623
|View full text |Cite
|
Sign up to set email alerts
|

CD4-Dependent and CD4-Independent Utilization of Coreceptors by Human Immunodeficiency Viruses Type 2 and Simian Immunodeficiency Viruses

Abstract: More than 10 G protein-coupled receptors (GPCRs) have been reported to act as coreceptors for entry of human and simian immunodeficiency viruses (HIV and SIV). We investigated the utilization of six GPCRs as coreceptors by T-cell-line-adapted HIV-2 strains (CBL-20, CBL-21, CBL-23, GH-1, ROD, and SBL6669) and SIV strains (SIVagmTYO-1, SIVmac251, and SIVmndGB-1). NP-2/CD4 cells were transduced with CCR3, CCR5, CCR8, CXCR4, GPR1, or APJ, and examined for susceptibilities to cell-free HIV/SIV. HIV-2 strains were g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
26
0
1

Year Published

2003
2003
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 32 publications
(28 citation statements)
references
References 52 publications
1
26
0
1
Order By: Relevance
“…SIVman4 is a T-cell-line-adapted variant of SIVsmB670 (51). The coreceptor use of most of the virus isolates used in this study has been previously described (46,54) and is summarized in Table 1. All virus stocks were propagated in PBMCs purified from whole blood by density gradient centrifugation and stimulated for 2 days in phytohemagglutinin (1 g/ml) (Sigma) and for 2 days in human recombinant IL-2 (20 U/ml) (Roche, Inc.), with the exception of GUN-1v, which was passaged in the T-cell line MOLT4 clone 8.…”
Section: Methodsmentioning
confidence: 99%
“…SIVman4 is a T-cell-line-adapted variant of SIVsmB670 (51). The coreceptor use of most of the virus isolates used in this study has been previously described (46,54) and is summarized in Table 1. All virus stocks were propagated in PBMCs purified from whole blood by density gradient centrifugation and stimulated for 2 days in phytohemagglutinin (1 g/ml) (Sigma) and for 2 days in human recombinant IL-2 (20 U/ml) (Roche, Inc.), with the exception of GUN-1v, which was passaged in the T-cell line MOLT4 clone 8.…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, several primary HIV-2 and SIV isolates have been shown to enter cells in a CD4-independent way [81,148,168,[176][177][178][179].…”
Section: Cd4-independent Infectionmentioning
confidence: 96%
“…(Schroder et al, 2002 (Dejucq et al, 1999;Dejucq, 2000), it may be difficult to estimate the exact coreceptor antagonisms. In contrast, NP-2 cells have been shown not to express any coreceptors for HIV Soda et al, 1999;Liu et al, 2000;Shimizu et al, 2000), suggesting that data obtained from NCK45 cells showed accurate coreceptor antagonisms. Indeed, coreceptor dependency of clinical isolates were easily evaluated in NP-2 derived cells (Witvrouw et al, 1992) (Chow et al, 1993;Schuetz et al, 1999;Villalba et al, 1999) (Chaillou et al, 2002;Zhu et al, 2004 …”
Section: The Activity Of Various Anti-hiv Agents Was Examined In Nck4mentioning
confidence: 97%